T1 bias in chemical shift‐encoded liver fat‐fraction: Role of the flip angle. Issue 4 (15th November 2013) - Kühn, Jens‐Peter; Jahn, Christina; Hernando, Diego; Siegmund, Werner; Hadlich, Stefan; Mayerle, Julia; Pfannmöller, Jörg; Langner, Sonke; Reeder, Scott
<x xml:space="preserve">Abstract</x> Purpose To investigate flip angle (FA)‐dependent T1 bias in chemical shift‐encoded fat‐fraction (FF) and to evaluate a strategy for correcting this bias to achieve accurate MRI‐based estimates of liver fat with optimized signal‐to‐noise ratio (SNR). Materials and Methods Thirty‐three obese patients, 14 men/19 women, aged 57.3 ± 13.9 years underwent 3 Tesla (T) liver MRI including MR‐spectroscopy and four three‐echo‐complex chemical shift‐encoded MRI sequences using different FAs (1°/3°/10°/20°). FF was estimated with R2* correction and multi‐peak fat spectral modeling. The FF for each FA with and without T1 correction was compared with spectroscopy as a reference standard, using linear regression. Relative SNR of the magnitude data were assessed for each flip angle. Results The correlation between chemical shift‐encoded MRI and spectroscopy was high (R2 ≈ 0.9). Without T1 correction, the agreement of both techniques showed no significant differences in slope (PFlipAngle1° = 0.385/PFlipAngle3° = 0.289) using low FA. High FA resulted in significant different slopes (PFlipAngle10° = 0.016/PFlipAngle20° = 0.014. T1 bias was successfully corrected using the T1 correction strategy (slope:PFlipAngle10° = 0.387/PFlipAngle20° = 0.440). Additionally, the use of high FA (near the Ernst angle) improved the SNR of the magnitude data (FA1 vs. FA3; respectively FA1 vs. FA10 P ≤ 0.001). Conclusion T1 bias is a strong confounder in the assessment of liver fat using chemical shift imaging with high FA. However, using a larger flip angle with T1 correction leads to higher SNR, and residual error after T1 correction is very small. J. Magn. Reson. Imaging 2014;40:875–883. © 2013 Wiley Periodicals, Inc.